2021
DOI: 10.21203/rs.3.rs-385310/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acircularity and Circularity Indexes of the Foveal Avascular Zone in High Myopia

Abstract: We explored the association between foveal avascular zone (FAZ) parameters and high myopia using optical coherence tomography angiography (OCTA). To evaluate the specific influence of high myopia on the FAZ, we divided 106 eyes of 106 patients into quartiles based on the axial length. The upper quartile was then defined as the high myopia group (n = 27), while the lower quartile was the non-high myopia group (n = 26). The FAZ parameters of these two groups were then retrospectively compared to investigate vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Additionally, FAZ area had an increasing trend with myopia severity. Previous studies have also shown that FAZ area was significantly enlarged in highly myopic eyes than in those with non-high myopia [32][33] . All myopic eyes exhibited thicker CRT and thinner CCT compared with that of emmetropic eyes.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, FAZ area had an increasing trend with myopia severity. Previous studies have also shown that FAZ area was significantly enlarged in highly myopic eyes than in those with non-high myopia [32][33] . All myopic eyes exhibited thicker CRT and thinner CCT compared with that of emmetropic eyes.…”
Section: Discussionmentioning
confidence: 75%
“…The high prevalence of myopia leads to an increased incidence of HM because of the relationship between these two diseases (Morgan et al, 2018). Excessive axial elongation is the most important pathological change in patients with HM; it can cause retinal detachment, choroidal neovascularization, macular hemorrhage, and retinal ischemia, all of which lead to impaired visual function (Piao et al, 2021). In clinical practice, resting-state functional magnetic resonance imaging (rs-fMRI) has recently received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of myopia remains unclear. 10 The choroid is a subretinal layer of the retina that can provide metabolic support for the retinal pigment epithelium, provide blood supply for the outer retina, and participate in lymphatic drainage. 11 Currently, we recognize that the choroid is a five-layered structure consisting (from the outside to the inside) of the basement membrane of the choriocapillaris, outer collagenous zone, elastic layer, inner collagenous zone, and basement membrane of the retinal pigment epithelium.…”
mentioning
confidence: 99%